Effects of heat treatment temperature on the morphology, composition, and electrocatalytic properties of electrodeposited NiB thin films towards OER. (10th March 2023) - Becerril-Estrada, V.; González-Gutiérrez, L.; Valdez-Nava, J.I.; Vazquez-Arenas, Jorge; Lara, René H.; Lartundo-Rojas, Luis; Manríquez, J.; Sepúlveda-Guzmán, S.; Ortega, R.; Méndez-Albores, A.; Trejo, G.
Highlights: Defects associated with oxygen vacancies were formed during the electrodeposition of NiB films. NiB thin film without heat treatment present efficiencies similar or superior to other catalysts commonly used for OER. The thermal treatment of NiB films promotes the formation of multiple phases (Ni2 B, Ni3 B and NiO) on the surface. The number of oxygen vacancies formed in NiB films decreased with heat treatment. The efficiency of NiB catalysts decreases with increasing heat treatment temperature. Abstract: In this study, we evaluate the textural properties, elemental composition, and electrocatalytic properties of NiB films formed by electrodeposition and thermal treatment at 520 and 650°C. The NiB films were characterized by thermogravimetric analysis (TGA), scanning electron microscopy (SEM), atomic force microscopy (AFM), glow discharge optical emission spectroscopy (GD-OES), X-ray diffraction (XRD) and X-Ray photoelectron spectroscopy (XPS). The morphology and composition of the NiB films were affected by the applied thermal treatment, showing an increase and decrease in oxygen and boron concentrations in the coatings, respectively. This behavior is associated with the decomposition of the NiB intermetallic compounds, as well as the formation of NiO with increasing temperature. In addition, the XPS analysis showed that the percentage of surface defects formed during the electrodeposition of the NiB films decreased after the thermal treatment of the samples. Linear voltammetry, chronoamperometry, and electrochemical impedance spectroscopy (EIS) were used to evaluate the electrocatalytic activity of the NiB films towards the oxygen evolution reaction (OER). NiB films without thermal treatment showed the lowest onset potential for the OER (1.47 V vs. RHE), overpotential to reach 10 mAcm −2 (400 mV), Tafel slope (68 mV dec −1 ), and charge transfer resistance (2.4 Ω). This finding reveals that the NiB electrocatalyst without thermal treatment presents similar or superior performance to other electrocatalysts reported in the literature, while the OER kinetics of the NiB electrocatalyst decreases after heat treating at 520 or 650°C, due to the NiB decomposition, decrease in the percentage of surface defects and NiO formation.